Global conservation strategy for Musa (Banana and Plantain): A consultative document prepared in collaboration with partners in the Musa research-and-development community. March 2006. - Rosales, F.E.; Belalcázar Carvajal, S.; Pocasangre, L.E. (2006)
This document presents a strategy to rationalize the conservation of the banana gene pool and promote the safe use and distribution of a wide range of diversity, all the way to farmers fields.